(3GdEOGQI GdEdcJQhfjI (B/s - (3GdUjQaj, eMeOs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2006)
(3GdMcheI GdGdcJQhfjI, GdCYeGd GdGdcJQhfjI, GdJShjb GdGdcJQhfjs
(3eQGLY U(B.789s
Keywords: (3GdGOGQIs; (3GdEOGQI(B- (3GdCLgRI GdEdcJQhfjI s; (3GdMcheGJs